"Logan circle arctic beauty" (Philadelphia Evening Bulletin, 1925)
"The season's first closeup of the ice-covered central group which consists of three reclining bronze figures symbolizing the Delaware and Schuylkill rivers and Wissahickon creek. The dome of S.S. Peter and Paul is [in] the background." With clipping